Work function and quantum efficiency study of metal oxide thin films on Ag(100) - Chang,V; Noakes,TCQ; Harrison,N (Physical Review B, 2018)
Increasing the quantum efficiency (QE) of metal photocathodes is in the design and development of photocathodes for free-electron laser applications. The growth of metal oxide thin films on certain metal surfaces has previously been shown to reduce the work function (WF). Using a photoemission model B. Camino [Comput. Mater. Sci. 122, 331 (2016)CMMSEM0927-025610.1016/j.commatsci.2016.05.025] based on the three-step model combined with density functional theory calculations we predict that the growth of a finite number of MgO(100) or BaO(100) layers on the Ag(100) surface increases significantly the QE compared with the clean Ag(100) surface for a photon energy of 4.7 eV. Different mechanisms for affecting the QE are identified for the different metal oxide thin films. The addition of MgO(100) increases the QE due to the reduction of the WF and the direct excitation of electrons from the Ag surface to the MgO conduction band. For BaO(100) thin films, an additional mechanism is in operation as the oxide film also photoemits at this energy. We also note that a significant increase in the QE for photons with an energy of a few eV above the WF is achieved due to an increase in the inelastic mean-free path of the electrons.